2004
DOI: 10.1074/jbc.m401602200
|View full text |Cite
|
Sign up to set email alerts
|

Notch1-expressing Cells Are Indispensable for Prostatic Branching Morphogenesis during Development and Re-growth Following Castration and Androgen Replacement

Abstract: Notch expression is frequently associated with progenitor cells, and its function is crucial for development. Our recent work showing that Notch1 is selectively expressed in basal epithelial cells of the prostate and higher Notch1 expression during development suggests that Notch1-expressing cells may define progenitor cells in the prostate. To test this hypothesis, we have generated a transgenic mouse line in which the Notch1-expressing cells can be ablated in a controlled manner. Specific targeting was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 59 publications
3
73
0
5
Order By: Relevance
“…A series of studies revealed that, apart from its well-documented involvement in cell fate decisions, Notch signaling could affect cellular proliferation (Deftos et al, 1998;Shelly et al, 1999;Satoh et al, 2004). During prostate develop- ment, Notch1-expressing cells defined the progenitor cells in the prostatic epithelial cell lineage, and ablation of Notch signaling in those cells inhibits the branching morphogenesis, growth, and differentiation (Wang et al, 2004). In the pancreas, disturbed branching morphogenesis also occurs in mice deficient in Fgf10 or its high-affinity receptor Fgfr2-IIIb (Bhushan et al, 2001;Pulkkinen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies revealed that, apart from its well-documented involvement in cell fate decisions, Notch signaling could affect cellular proliferation (Deftos et al, 1998;Shelly et al, 1999;Satoh et al, 2004). During prostate develop- ment, Notch1-expressing cells defined the progenitor cells in the prostatic epithelial cell lineage, and ablation of Notch signaling in those cells inhibits the branching morphogenesis, growth, and differentiation (Wang et al, 2004). In the pancreas, disturbed branching morphogenesis also occurs in mice deficient in Fgf10 or its high-affinity receptor Fgfr2-IIIb (Bhushan et al, 2001;Pulkkinen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…57 Although there is no evidence for an involvement for Notch signalling in human prostate stem-cell regulation, a recent study showed that Notch1 is highly expressed in basal cells during prostate development. 58 Wang and colleagues also showed that Notch1 is downregulated in adult tissue but is upregulated in some cells during tumorigenesis of the TRAMP mouse model. 59 Notch1 was also required for branching morphogenesis during development as well as regeneration following androgen ablation.…”
Section: Notch/deltamentioning
confidence: 99%
“…Among these, the Notch signaling pathway, which is present in most multicellular organisms, plays a role in cancer metastasis by governing embryonic development, maintaining tumor stemness, modulating the epithelial-to-mesenchymal transition (EMT), and affecting tumor angiogenesis processes (12)(13)(14). Several studies have demonstrated that the Notch signaling pathway is required for prostatic growth and plays a key role in the progression and metastasis of prostate cancer (15)(16)(17). It had been proved that the expression of both Notch receptors and their ligands would be upregulated in many prostate cancer cells compared with normal prostate cells (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%